Search for second-generation scalar leptoquarks in pp̄ collisions at s=1.96TeV - Abulencia, A; Acosta, D; Adelman, J; Affolder, T; Akimoto, T; Albrow, MG; Ambrose, D; Amerio, S; Amidei, D; Anastassov, A; Anikeev, K; Annovi, A; et al. (2006)
Results on a search for pair production of second-generation scalar leptoquark in pp̄ collisions at s=1.96TeV are reported. The data analyzed were collected by the CDF detector during the 2002-2003 Tevatron Run II and correspond to an integrated luminosity of 198pb-1. Leptoquarks (LQ) are sought through their decay into (charged) leptons and quarks, with final state signatures represented by two muons and jets and one muon, large transverse missing energy and jets. We observe no evidence for LQ production and derive 95% C.L. upper limits on the LQ production cross sections as well as lower limits on their mass as a function of β, where β is the branching fraction for LQ→μq. © 2006 The American Physical Society.